Between Practice and Perception: Formative Assessment Used by EFL Novice Teachers and Students’ Responses toward the Implementation in Offline Classroom Mode - Zahrotuz Zainiah; Syafi'ul Anam; Tengsoe Tjahjono (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. This study aims to 1) investigate the ways of EFL novice secondary school teachers conducted Formative Assessment (FA) in offline classroom mode 2) investigate its implementation based on the five key strategies of FA 3) reveal students’ responses toward teachers’ implementation of FA in the classroom. The participants of this study were five EFL novice teachers and five students of several secondary schools in East Java, Indonesia. This study employed qualitative research and semi-structured interview to collect the data. Results showed that teachers use various ways to conduct the FA in the classroom, such as giving quizzes, observing the students’ attitudes, asking the students to make learning diary, and asking them to do self-assessment. It is also noted that the teachers employed the five keys strategies of FA, even though there is still a limitation found in the first strategy. Furthermore, students perceive the teachers’ implementation of FA both in positive and negative ways. Students also found that there are benefits of FA that they can grasp such as the awareness of their capability, as well as the sense of achievement that maybe helpful to grow their sense of responsibility to their learning experience.Keywords: EFL Classroom; EFL Novice Teachers; Formative Assessment; Students’ Perception